Spotlight on sweetpotato in the context of roots, tubers and bananas - International Potato Center (2017)
The CGIAR Research Program on Roots, Tubers and Bananas (RTB) is an alliance led by the International Potato Center implemented jointly with Bioversity International, the International Center for Tropical Agriculture (CIAT), the International Institute of Tropical Agriculture (IITA), and the Centre de Coopération Internationale en Recherche Agronomique pour le Développement (CIRAD), that includes more than 350 partners for research on banana, cassava, potato, sweetpotato, yam, and minor roots and tubers. The program has two dedicated clusters of activity on sweetpotato, led by CIP scientists, that will interact with, learn from, and add critical mass to RTB’s other work.